Na2SeO3: A Na-Ion Battery Positive Electrode Material with High Capacity. Issue 3 (21st November 2018) - Su, Bizhe; Zhang, Jiaolong; Fujita, Manabu; Zhou, Wenchong; Sit, Patrick H.-L.; Yu, Denis Y. W.
Abstract : Recent experimental and theoretical studies on the family of Li-rich layered materials show that they can deliver much higher capacities than traditional Li-transitional metal oxides. This also leads to great interests in Na-rich layered oxides as alternative positive electrode materials for sodium-ion batteries for large-scale energy storage. Herein, we report a Na-rich material, Na2 SeO3 with an unconventional layered structure as a positive electrode material in NIBs for the first time. This material can deliver a discharge capacity of 232 mAh g −1 after activation, one of the highest capacities from sodium-based positive electrode materials. X-ray photoelectron spectroscopy indicates the oxidation state of selenium remains unchanged during the charge process. Theoretical simulation shows that after removal of Na, spin is situated around oxygen atoms near the Na vacancy, and the projected density of state of oxygen electron is close to the Fermi level. These suggest the involvement of oxygen during charge-discharge. This work will propel new searches of high-capacity sodium-based positive electrode materials.